Lupeol and its esters: NMR, powder XRD data and in vitro evaluation of cancer cell growth - Aline Teixeira Maciel e Silva; Cássia Gonçalves Magalhães; Lucienir Pains Duarte; Wagner da Nova Mussel; Ana Lucia Tasca Gois Ruiz; Larissa Shiozawa; João Ernesto de Carvalho; Izabel Cristina Trindade; Sidney Augusto Vieira Filho (Universidade de São Paulo, 2018)
ABSTRACT The triterpene lupeol (1) and some of its esters are secondary metabolites produced by species of Celastraceae family, which have being associated with cytotoxic activity. We report herein the isolation of 1, the semi-synthesis of eight lupeol esters and the evaluation of their in vitro activity against nine strains of cancer cells. The reaction of carboxylic acids with 1 and DIC/DMAP was used to obtain lupeol stearate (2), lupeol palmitate (3) lupeol miristate (4), and the new esters lupeol laurate (5), lupeol caprate (6), lupeol caprilate (7), lupeol caproate (8) and lupeol 3',4'-dimethoxybenzoate (9), with high yields. Compounds 1-9 were identified using FT-IR, 1H, 13C-NMR, CHN analysis and XRD data and were tested in vitro for proliferation of human cancer cell activity. In these assays, lupeol was inactive (GI50> 250µg/mL) while lupeol esters 2 -4 and 7 - 9 showed a cytostatic effect. The XRD method was a suitable tool to determine the structure of lupeol and its esters in solid state. Compound 3 showed a selective growth inhibition effect on erythromyeloblastoid leukemia (K-562) cells in a concentration-dependent way. Lupeol esters 4 and 9 showed a selective cytostatic effect with low GI50 values representing promising prototypes for the development of new anticancer drugs.